Implementation and Development of Qur’an Learning Method in Malaysia and Indonesia: An Analysis - Jaafar, Azhar; K, Munawir; Hamzah, Mohd Isa (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2017)
The article aimed to analyze the implementation and development of Qur’an learning methods in two cognate countries, Malaysia and Indonesia. The methodology used was content analysis, one of the research approaches in qualitative research. Data came from the author’s reading of various theories, expert opinions, and research results of previous researchers associated with education and learning of the Qur’an. All data is then collected, reduced, presented, and closed with conclusions. In the beginning, the authors begin with the introduction, further discuss the urgency of learning and teaching of Qur’an, the method of learning the Qur’an in the first period of Qur’an is revealed, the obligation to read the Qur’an well and correctly, the description of methods and analysis of the implementation of learning Qur’an in Malaysia and Indonesia, factors that influence the success of learning Qur’an and conclude with conclusions. The results of the discussion of this article can at least be an additional reference material for Qur’an observers teachers Qur’an in particular, parents, the community, and the next researchers related to the study of Qur’an in Islamic education.